2014
DOI: 10.2478/hukin-2014-0093
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Resistance Training on Blood Pressure in Patients with Metabolic Syndrome and Menopause

Abstract: This study investigated the chronic and acute influence of resistance exercise on blood pressure in women with metabolic syndrome before and after climacteric. Twenty sedentary women, nine non-menopausal (RNM) and 11 menopausal (RM), performed training for 12 weeks. Meanwhile, 23 controls, 11 not menopausal (CNM) and 12 menopausal (CM), remained sedentary. Blood pressure was measured before and after the training period in conditions of rest and after a session of exercise. Training promoted variations in bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 26 publications
(32 reference statements)
0
6
0
6
Order By: Relevance
“…Several studies have shown that aerobic exercise training of mild or moderate intensity is effective in reducing BP by improving baroreflex control of HR significantly in hypertensive rats, as well as controlling risk factors associated with hypertension. 9 - 11 Although there is no consensus in the literature on the effects of resistance training on BP, 12 - 14 practicing this type of training can be beneficial to hypertensive patients, especially elderly people, since muscle strength decreases with age, thus decreasing the quality of life. 15 Therefore, the aim of this study was to evaluate the effect of resistance exercise training on BP and the sensitivity of baroreceptor in spontaneously hypertensive rats (SHR).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that aerobic exercise training of mild or moderate intensity is effective in reducing BP by improving baroreflex control of HR significantly in hypertensive rats, as well as controlling risk factors associated with hypertension. 9 - 11 Although there is no consensus in the literature on the effects of resistance training on BP, 12 - 14 practicing this type of training can be beneficial to hypertensive patients, especially elderly people, since muscle strength decreases with age, thus decreasing the quality of life. 15 Therefore, the aim of this study was to evaluate the effect of resistance exercise training on BP and the sensitivity of baroreceptor in spontaneously hypertensive rats (SHR).…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is the absence of a pure control group comprised of sedentary participants, since this group was submitted to a stretching program that could have promoted some cardiovascular adaptations, although this was not observed in our study. Although all the women were post-menopausal, we did not control how long they were in this phase; however, a recent study observing the effect of a resistance training program on post-resistance exercise responses did not find significant differences between pre-and postmenopausal women (Cardoso et al 2014). …”
Section: Discussionmentioning
confidence: 95%
“…Comorbidity may lead to poor health-related outcomes [ 39 ]. Subjects with metabolic syndrome may contribute to lower BP reduction after PA treatment [ 40 , 41 ]. The change in BP during exercise is strongly associated with serum TC level and insulin resistance [ 42 ].…”
Section: Discussionmentioning
confidence: 99%